RakBuku: Konsep user interface aplikasi untuk menemukan dan mengelola koleksi bacaan - Husna, Faiza Arifatul (Maliki Interdisciplinary Journal, 2025)
he development of digital platforms to facilitate access to book collections has become essential in the digital era. RakBuku is a Flutter-based mobile application designed to help users find, store, and recommend books based on preferences. Key features include an intuitive user interface, a bookmarking system, and categorized book recommendations. With further development, RakBuku is expected to become a more comprehensive and interactive platform for book enthusiasts.